2018
DOI: 10.1080/08990220.2018.1432481
|View full text |Cite
|
Sign up to set email alerts
|

Oral curcumin supplementation improves fine motor function in the middle-aged rhesus monkey

Abstract: Aged individuals experience decreased fine motor function of the hand and digits, which could result, in part, from the chronic, systemic state of inflammation that occurs with aging. Recent research for treating age-related inflammation has focused on the effects of nutraceuticals that have anti-inflammatory properties. One particular dietary polyphenol, curcumin, the principal curcuminoid of the spice turmeric, has been shown to have significant anti-inflammatory effects and there is mounting evidence that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 120 publications
(159 reference statements)
2
13
0
Order By: Relevance
“…However, the present study observed increase in motor score of rats treated with curcumin regardless of the dose given. Moore et al [35], also observed a similar findings and attributed it to the antioxidant and anti-inflammatory properties of curcumin on motor function.…”
Section: Discussionmentioning
confidence: 57%
“…However, the present study observed increase in motor score of rats treated with curcumin regardless of the dose given. Moore et al [35], also observed a similar findings and attributed it to the antioxidant and anti-inflammatory properties of curcumin on motor function.…”
Section: Discussionmentioning
confidence: 57%
“…Chronic nonspecific neck pain (CNNP) is a widespread public health problem in the modern world, [1] with a reported prevalence of 50% lifetime prevalence [2] and more and more frequent in adolescence. [3] CNNP is considered as persistent neck pain or severe discomfort in the neck for over 3 months, [4] which is caused by poor posture and mechanical and degenerative changes, excluding pain from neck cancer, infections fasciitis, or other areas of the body.…”
Section: Introductionmentioning
confidence: 99%
“…However, the present study observed increase in motor score of rats treated with curcumin regardless of the dose given. Moore et al [41], also observed a similar findings and attributed it to the antioxidant and anti-inflammatory properties of curcumin on motor function. Chongtham and Agrawal [42] also reported that curcumin ameliorates disease symptoms in Drosophila model of Huntington disease (HD).…”
Section: Discussionmentioning
confidence: 57%